A Comparative assessment of Dorper sheep in different production environments and systems - Schoeman, S.J. (Elsevier, 2000)
Performance of Dorper sheep was compared to other breeds in pure and cross-breeding evaluations under different production systems. The number of ewes lambed per ewe joint (EL/ Ej) varied for the Dorper from 0.68 to 0.91 (average 0.81) and for other breeds and crosses from 0.65 to 0.91 (Average 0.82). Average litter size (LB/lambing) varied from 1.02 to 1.52 (average 1.28) and from 1.02 to 1.70 (average 1.30) for the two groups, respectively rates in Kenya were high (49%) among Dorper lambs compared to the local red Maasai breed. Owing to a high susceptibility to gastrointestinal parasites. Average weaning weight (WW) (100 days) were 12.4% heavier in the Dorper. Post-weaning mortality rates in Kenya were high (49%) among Dorper lambs compared to the local Red Maaisai breed, owing to a high susceptibility to gastrointestinal parasites. Average weaning weights (WW) (100days) were 12.4% heavier in the Dorper than in the breeds it was compared to, but 31.7% heavier than the woolled breeds. Total WW and efficiency of Dorper and Dorper crosses were higher than Merino, Afrino, Dohne merino, South African Mutton Merino, but lower than in Finnish Landrace composite lines. Both Dorper and Dorper cross-breeds reached target slaughter weight of approx. 40kg earlier than Merino, Afrino, Suffolk and Ile de France crosses. Average daily gain to slaughter was 44% higher in the Dorper than the average of the groups it was compared to. It is concluded that the Dorper was superior in reproductive and growth traits to woolled and other indigenous breeds. However, there is a lack of information on the performance of the Dorper in cross-breeding systems.